NEOLOGISME DALAM MEDIA SOSIAL: KAJIAN MORFOSEMANTIK - Satriani, Satriani (Universitas Hasanuddin, 2021)
This study aims to describe the types of Indonesian neologisms found in social media. This research is qualitative research with a morphosemantic approach. The neologisms that are the data in this study are contemporary words summarized in various articles. Data was collected using the observation method. Data analysis using distributional methods. The results of this study indicated four types of neologisms, namely 1) morphosemantic neologisms; 2) morphological neologisms; 3) semantic neologisms; and 4) borrowing neologisms. Neologisms in social media are generally basic words. This suggest that language users need a more concise word form.